Ethnolinguistic Vitality of Manide Tribe: Basis for Proposing Educational Material Plan - Abad, Delma Jean V.; Abad, Eduardo M. (International Journal of Language and Literary Studies, 2022)
This study determined the vitality of the language of Manide and the practices they observe to preserve it. This study utilized the descriptive research method. A semi-structured interview was conducted using the Indicators of Ethnolinguistic Vitality Review and Score Sheet as a survey checklist for 20 elders, adults, and youth Manide respondents. The data gathered were transcribed and thematically analyzed through manual Vivo coding. Results revealed that although more tribe members comprised of youth, adults and elders are inclined to use their language in day-to-day conversation, there are factors that caused them to shift to Tagalog; thus, based on Indicators of Ethnolinguistic Vitality (IEV), there is a probable shift in process in their language. Further, maintaining the use of language and shifting only when the needs arise, Documenting songs in Manide with translations in Tagalog, Creating Manide pieces for performances during events, and Teaching the Tradition to the young generation are four the disclosed practices they observe to maintain their language. Although these posited practices were found to help maintain the viability of the Manide language, there is still a need to create tangible support to preserve it against the identified threats. Consequently, out of the analysis of the current language status, an Educational material plan has been crafted with the concepts: Language exposure, Literary piece creation, Generational transmission of tradition, and Education continuum as its main components. These generated language preservation concepts are believed to be an initial step to protecting the Manide language of the tribe.